AN ANALYSIS OF FIGURATIVE LANGUAGE IN ONLINE SHORT STORY POSTED ON THE JAKARTA POST - Radna Tulus Wibisono; Pratomo Widodo (Linguistik : Jurnal Bahasa dan Sastra, 2019)
This research entitled ”An Analysis of Figurative Language in Onlen Short Story Posted on The Jakarta Post” is aimed to found some kinds of figurative language used; she also studies about the meaning of figurative language used in selected short story on online the Jakarta  Post. This research employs the library research in the sense that the researcher visited the libraries to get the data. There are two kinds of data in this research: (1) primary sources and (2) secondary sources. Primary source is firsthand information. Then secondary sources provide secondhand information. In this study, the primary source is short story gained from online Jakarta Post. Then, the secondary source was from books, e-books, journals, English dictionary, observation and documentation that were related to the research which was gained. After the data are gathered, they classified, analyzed, and interpreted by using several theories namely: (1) the theory of Figurative Language by Perrine (1982:61)), Short Story by Klarer (1998:13). Some of the important research findings are presented as follows. First, figurative language has many types, such as metaphor, simile, personification, metonymy, irony, symbol, hyperbole, paradox, alliteration, allusion, onomatopoeia, and many others. Henceforth, all kinds of figurative language cannot be found in all work of literature. There are some types mostly found in the literature, such as simile, personification, hyperbole, metaphor, irony, and metonymy. In this case, the writer only conducted the research in short story. The writer found some types of figurative language in the short story; those are personification, simile, symbol, and onomatopoeia. Personification is one of types of figurative language mostly found in the short story posted on online Jakarta Post. Keywords: Figurative, language, Jakarta post